Optimalisasi Potensi Desa Tua Menuju Pengembangan Pariwisata Berkelanjutan: Studi Kasus Desa Wisata Julah - Rona, I Wayan; Widiastini, Ni Made Ary; Suarmanayasa, I Nengah; Suci, Ni Made (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p18, 2022)
The Indonesian government considers the tourism sector as one of the high contributors to the national economy. As one of them that supports tourism, especially talk about Tourism Villages, is the Ministry of Tourism and Creative Economy (Kemenparekraf) through a program released recently about ADWI 2022. Julah Tourism Village is one of the highlights that should be developed in the future as sustainable tourism. This research uses qualitative research by primary and secondary data in Julah Village. In primary data, data collection is through direct observation and interviews, while secondary data is collected through several studies, articles, and related literature. In this study, it was found that the development of sustainable tourism was not optimal. So far, tourism potential has been highly conserved but along with modernization and globalization, this can trigger the erosion of tourism potential which has an impact on unsustainability. Therefore, it is necessary to improve tourism development strategies towards sustainable tourism. Keywords: julah, optimization, sustainable tourism.